“No drain” uniportal thoracoscopic resection for posterior mediastinal paravertebral Mullerian cyst - Tsai, Ping-Chung (Ann Transl Med, 2018)
Mediastinal Mullerian cyst was first reported by Hattori in 2005. We report a case of a posterior mediastinal paravertebral cyst found incidentally by surveillance chest roentgenogram in a 44-year-old woman. She had a “no drain” uniportal thoracoscopic removal procedure, and histologic examination showed single layer of columnar epithelial lining that stained positive for estrogen receptors (ER), progesterone receptors (PR), paired box gene 8 (PAX8), and Wilms’ tumor protein 1 (WT-1), confirming the diagnosis of mediastinal Mullerian cyst.